TRAYEK ANGKUTAN UMUM UNTUK MENGOPTIMALKAN INTERAKSI DESA KOTA DI KABUPATEN BOYOLALI - Wimas Hasan Febrianto; Saptono Putro; Hariyanto Hariyanto (Geo-Image, 2017)
This study aims are to 1) determine the travel pattern of the population movement from the rural to the urban areas through the information of the source travel destination, purpose to do the travel, time to is affected by the activities and the use of field. 2) to determine the value of loading factor of public transportation in Boyolali Regency. 3) to determine which region having strong or weak attraction/generation of trip. The techniques that use for collecting data through by the observation, interview, and documentation. The data that has been gotten then can be processed using the Likert and Gutman scale technique.Based on the result of this study, our society need comfortable general transportation tool. In other way, society also want the goverment to create a ne trajectory paths in the region that has not yet passed by the public transportation.